Patient-reported outcomes with first-line nivolumab plus cabozantinib versus sunitinib in patients with advanced renal cell carcinoma treated in CheckMate 9ER: an open-label, randomised, phase 3 trial. Issue 2 (February 2022) - Cella, David; Motzer, Robert J; Suarez, Cristina; Blum, Steven I; Ejzykowicz, Flavia; Hamilton, Melissa; Wallace, Joel F; Simsek, Burcin; Zhang, Joshua; Ivanescu, Cristina; Apolo, Andrea B; Choueiri, Toni K
Summary: Background: In the CheckMate 9ER trial, patients with advanced renal cell carcinoma who received first-line nivolumab plus cabozantinib had significantly better progression-free survival compared with those given sunitinib. In this study, we aimed to describe the patient-reported outcome (PRO) results from CheckMate 9ER. Methods: In this open-label, randomised, phase 3 trial done in 125 cancer centres, urology centres, and hospitals across 18 countries, patients aged 18 years or older with previously untreated advanced renal cell carcinoma with a clear-cell component, a Karnofsky performance status of 70% or more, and available tumour tissue were randomly assigned (1:1) via interactive response technology to nivolumab 240 mg intravenously every 2 weeks plus oral cabozantinib 40 mg per day, or oral sunitinib 50 mg per day monotherapy for 4 weeks in 6-week cycles. The primary endpoint of progression-free survival was reported previously. PROs were analysed as prespecified exploratory endpoints at common timepoints (at baseline and every 6 weeks) until week 115. Disease-related symptoms were evaluated using the 19-item Functional Assessment of Cancer Therapy-Kidney Symptom Index (FKSI-19), and global health status was assessed with the three-level EQ-5D (EQ-5D-3L) visual analogue scale (VAS) and UK utility index. PRO analyses were done in the intention-to-treat population. Change from baseline was assessed using mixed-model repeated measures. A time-to-deterioration analysis was done for first and confirmed deterioration events. This study is registered with ClinicalTrials.gov, NCT03141177, and is closed to recruitment. Findings: Between Sept 11, 2017, and May 14, 2019, 323 patients were randomly assigned to nivolumab plus cabozantinib and 328 to sunitinib. Median follow-up was 23·5 months (IQR 21·0–26·5). At baseline, patients in both groups reported low symptom burden (FKSI-19 disease-related symptoms version 1 mean scores at baseline were 30·24 [SD 5·19] for the nivolumab plus cabozantinib group and 30·06 [5·03] for the sunitinib group). Change from baseline in PRO scores indicated that nivolumab plus cabozantinib was associated with more favourable outcomes versus sunitinib (treatment difference 2·38 [95% CI 1·20–3·56], nominal p<0·0001, effect size 0·33 [95% CI 0·17–0·50] for FKSI-19 total score; 1·33 [0·84–1·83], nominal p<0·0001, 0·45 [0·28–0·61] for FKSI-19 disease-related symptoms version 1; 3·48 [1·58–5·39], nominal p=0·0004, 0·30 [0·14–0·47] for EQ-5D-3L VAS; and 0·04 [0·01–0·07], nominal p=0·0036, 0·25 [0·08–0·41] for EQ-5D-3L UK utility index), reaching significance at most timepoints. Nivolumab plus cabozantinib was associated with decreased risk of clinically meaningful deterioration for FKSI-19 total score compared with sunitinib (first deterioration event hazard ratio 0·70 [95% CI 0·56–0·86], nominal p=0·0007; confirmed deterioration event 0·63 [0·50–0·80], nominal p=0·0001). Interpretation: PROs were maintained or improved with nivolumab plus cabozantinib versus sunitinib. Compared with sunitinib, nivolumab plus cabozantinib significantly delayed time to deterioration of patient-reported outcome scores. These results suggest a benefit for nivolumab plus cabozantinib compared with sunitinib in the treatment of patients with advanced renal cell carcinoma. Funding: Bristol Myers Squibb.